Death of a parent transition to a new adult identity - Umberson, Debra (Cambridge University Press, 2003)
When a parent dies, most adults are seized by an unexpected crisis that can trigger a profound transformation of their beliefs, behavior, goals, and sense of self. Whether - and how - this loss is resolved can affect adults for the rest of their lives. Unlike other books on this topic, Death of a parent relies on national data as well as in-depth interviews to explore the social and psychological risk factors that make some people more vulnerable than others to depression, alcoholism, a weakened immune system, and other forms of personal crisis following this important loss. Dr. Umberson also looks at protective factors that help some individuals experience better mental health following the death than they did when the parent was alive. With the help of this book, readers will come to view the loss of a parent in a new way: as a turning point in adult development.